2022
DOI: 10.1186/s12909-022-03127-x
|View full text |Cite
|
Sign up to set email alerts
|

How technology-enhanced experiential e-learning can facilitate the development of person-centred communication skills online for health-care students: a qualitative study

Abstract: Background The COVID-19 pandemic brought a new challenge to medical education—health-care students had fewer opportunities to interact with and treat real patients in clinical settings. Interpersonal communication skills are often developed through human interaction and communication in person, and few studies have proposed feasible digital solutions to develop learners’ communication skills. Consequently, understanding how medical teachers facilitate and implement online training programmes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The integration of technology in educational practices is not merely a response to contemporary needs but a forward-looking approach to pedagogy. Studies have shown that educators' proficiency in digital tools significantly impacts the quality and efficacy of elearning environments (Liao et al, 2022;Ismail & Din, 2022;Marnita, Nurdin, & Prihatin, 2023). The ability of educators to effectively utilize digital platforms for teaching and learning extends beyond basic technological skills.…”
Section: Recommendations Educators A) Adaptation To Digital Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of technology in educational practices is not merely a response to contemporary needs but a forward-looking approach to pedagogy. Studies have shown that educators' proficiency in digital tools significantly impacts the quality and efficacy of elearning environments (Liao et al, 2022;Ismail & Din, 2022;Marnita, Nurdin, & Prihatin, 2023). The ability of educators to effectively utilize digital platforms for teaching and learning extends beyond basic technological skills.…”
Section: Recommendations Educators A) Adaptation To Digital Toolsmentioning
confidence: 99%
“…The adaptation to and integration of digital tools in education is a critical step towards enhancing the effectiveness of e-learning. It requires a concerted effort in training educators, not just in the use of technology, but in the integration of these tools into effective and innovative teaching practices (Liao et al, 2022;Ismail & Din, 2022;Marnita, Nurdin, & Prihatin, 2023).…”
Section: Recommendations Educators A) Adaptation To Digital Toolsmentioning
confidence: 99%
“…Salah satu jenis pendidikan yang saat ini kurang mendapat perhatian di sekolah adalah outdoor education. Peningkatan penekanan pada kemampuan bagi anak-anak untuk mengenali alam dan secara aktif dan berpartisipasi dengan lingkungan di luar.Selain itu, ingin mendapatkan pemahaman yang lebih baik tentang 'pengalaman' sebagai konsep utama pembelajaran dan pada akhirnya menemukan cara untuk memperbaiki dan meningkatkan peluang yang dapat saya diberikan anak-anak untuk mencapai potensi penuh mereka (Liao et al, 2022).…”
Section: Pendahuluanunclassified
“…Health services with patients directly become constrained because of restrictions on the mobility of people around the world. As a solution, online teaching was introduced to decrease physical contact and minimalizing COVID-19 transmission [ 12 ]. However, medical students argued that this method decreased study outcome quality, the emergence of psychological disorders, and fatigue [ 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%